Eccentric bearing capacity of embedded strip footings placed on slopes. (March 2020) - Li, Chengchao; Zhou, Aizhao; Jiang, Pengming
Abstract: The bearing capacity of strip footings placed on slopes is determined by slope geometry, soil strength and foundation distribution. Previous analyses for the ultimate bearing capacity of footings placed on slopes mainly focus on the fist two factors, and the influence of embedded soils and eccentric surcharges is rarely discussed. In this study, the eccentric bearing capacity of embedded strip footings placed on slopes is addressed by applying the finite element limit analysis method. Effective parameters, including an embedded depth ratio and an eccentric ratio, on the bearing capacity are examined. Design charts are provided to evaluate the eccentric bearing capacity of embedded footings as a function of dimensionless parameters. In addition, the ultimate bearing capacity predicted by the finite element limit analysis method is compared with that obtained by the existing methods.